PENGARUH PENDEKATAN CTL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA KELAS V PONTIANAK TIMUR - Wulandari, Nopi; Kartono, Kartono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to analyze and prove the influence of the Contextual Teaching and Learning approach on student learning outcomes in Natural Sciences learning in fifth grade ofÂ the State Elementary School 09 East Pontianak. The research method used was an Experiment, a form of Quasi Experimental type of Non Equivalent Control Group Design. The sampling technique used Purposive Sampling. The technique used in data collection is measurement. Data collection tool used is a test. The results of data analysis are, the average score of the experiment class 68.55 learning outcomes and the control is 60.71. After the t-test is obtained tcount (4.38) > ttable (1.99933) then Ha is accepted which indicates a difference significantly between the learning outcomes of the experimental class and the control class, which means that there is an influence of the contextual teaching and learning approach to student learning outcomes in Natural Sciences learning in fifth grade of the State Elementary School 09 East Pontianak. From the calculation of the effect size (ES) obtained at 0.68. This means that the contextual teaching and learning approach has a medium influence on student learning outcomes in Natural Sciences learning in the fifth grade of State Elementary School 09 East Pontianak.Â Keywords: Contextual Teaching and Learning Approaches, Learning Outcomes, Natural Sciences